Passeios hamletianos com Cortázar e Antonioni: incursões metaficcionais, narrativas à beira da paralisia - Silva, Cícera Antoniele Cajazeiras da (2017)
The present work studies the formal mechanisms and meanings of metafictional discourse in the short story Las babas del Diablo, by Julio Cortázar, and its implications in the adaptation process of Blow-up, a film by Michelangelo Antonioni. Based on theoretical principles on metafiction elaborated by Linda Hutcheon, Gustavo Bernardo, Patricia Waugh and Mark Currie, we perceive that in the short story, metafictionality is explicitly developed, constructing the impression that the narrative flow is on the verge of paralysis. Considering that this aspect affects the story’s narrative, we aim at verifying, based on Robert Stam’s studies on reflexivity in the cinema, in what way the process of adaptation deals with the difficulties imposed by the obliteration of narrativity inherent to the development of a self-reflexive cinematographic code and discourse. The theoretical studies by Seymour Chatman, Linda Hutcheon, Jacques Aumont, and Robert Stam support the analysis of the ways cinematographic language operates to incorporate self-reflexivity into filmic discourse. In this way, we intend to emphasize the metafictionality of Cortazar’s short-story as a crucial aspect to its signification, besides contributing to the studies of film adaptation in a metafictional context.